Increased estrogen levels altered microRNA expression in prostate and plasma of rats dosed with sex hormones. (20th March 2020) - Nakamura, Noriko; Davis, Kelly; Yan, Jian; Sloper, Daniel T.; Chen, Tao
Abstract: Background: Elevated estrogen (E) levels caused by aging or exposure to endocrine disrupting chemicals are related to prostate disease development. Sixty to seventy percent of prostate cancer or benign prostatic hyperplasia patients are over the age of 65, while prostatitis is likely to occur in men under 45 years. MicroRNAs currently represent a class of distinctive biological indicators to be used for clinical disease diagnosis and treatment monitoring. This study aims to identify microRNAs that could serve as potential biomarkers for prostate disorders induced by elevated E levels according to their altered expression in prostate or plasma. Materials and methods: Groups of Sprague Dawley rats (offspring) were dosed with estradiol benzoate (EB) on postnatal days 1, 3, and 5, and subcutaneously implanted with tubes containing testosterone (T)/E on postnatal day 90. Expression levels of prostate and plasma microRNAs were evaluated using microRNA microarray and validated via qRT‐PCR. The expression levels of the potential targeted genes of a set of identified microRNAs were also examined by qRT‐PCR. Results: Postnatal administration of EB, T, and E elevated serum E levels with decreased serum T levels in rats. Chronic inflammation was observed in the dorsolateral prostate. Significant changes in expression levels of several microRNAs (rno‐miR‐146‐5p, rno‐miR‐329‐3p, and rno‐miR‐126a‐3p) in the dorsolateral prostate and of a microRNA (rno‐miR‐329‐3p) in the plasma were found in the dosed rats. The target gene expression levels of the altered microRNAs also changed accordingly. Conclusion: Chronic inflammation in the dorsolateral prostate of rats dosed with EB, T, and E resulted in deregulated expression in a set of microRNAs whose target genes were related to tumor growth or abnormal proliferation. Our findings suggest the identified microRNAs and their target genes the potential use as biomarkers to predict prostate cancer development. Validation using human samples is warranted.